High-sensitivity two-photon absorption microcavity autocorrelator - Bradley, Louise; Donegan, John (My University, 2004)
A GaAs-AlAs microcavity device has been used as a photodetector in an autocorrelator for measuring the temporal pulsewidth of 1.5-/spl mu/m optical pulses. Enhancement of the two-photon absorption photocurrent due to the microcavity structure results in an autocorrelation (average power times peak power) sensitivity of 9.3/spl times/10/sup -4/ (mW)/sup 2/, which represents two orders of magnitude improvement when compared with conventional autocorrelators
PUBLISHED
Keywords: autocorrelator